Circulating economic ideas: adaptation, appropriation, translation - Cardoso, José Luís (2017)
The writing of this chapter was originally motivated by the general theme of the 4th ESHET Latin American Conference held in Belo Horizonte in November 2014, under the heading of Originality, Adaptation and Critique: the Place of Latin America in the History of Economic Thought. The conference featured a round table on the topic of the "International Dissemination of Economic Ideas." These notes correspond to the attempt that was made to promote the discussion of a few ontological and methodological issues related to the study of the spread and diffusion of economic ideas across countries and continents. This research subject is of utmost relevance for countries and regions that are usually seen as net importers of original ideas created abroad. Notwithstanding the capacity to build up creative thinking in Latin American countries, especially as regards original contributions to the theories and policies of economic development, there is plenty of evidence of the richness of the procedures involved in the critical adaptation and appropriation of economic knowledge. The scholarly debates on the diffusion in many Latin American countries of Enlightenment ideas on economic reform, Adam Smith's political economy, List's system of national political economy, or Keynesian economic policies - to name just the obvious and well-studied cases - offer multiple reasons for claiming the relevance of studies of this kind in the dissemination of economic thought.r The development of economic ideas and theoretical constructs in particular regional contexts is socially and politically determined, thus inviting historians to explain why, when, and how the spread and diffusion processes occurred. The aim of this contribution is to highlight a few points that help to understand this relevant issue in the historiography of economic thought. After a brief summary of canonical interpretation so I shall explore less cultivated territories of research, crossing borders within the universe of the social sciences.